Effective corporate board structure and agency problems: Evidence from China’s economic transition - Zhang, C.; Cheong, K.C.; Rasiah, R.; Zhang, C. (Institute of China Studies, 2016)
This study investigates the determinants of Chinese board structure during the economic transition from the year 2000 to 2012. It uses principal component analysis with fixed effects estimation to test three hypotheses – the scope of operation hypothesis, monitoring hypothesis and bargaining hypothesis – using different subsamples. Explained without the use of mathematical rigor, the paper’s main findings are that Chinese stock market liberalization and the ultimate controlling shareholder are important factors when constituting board structure. After the split-share structure reform, China tends to have an outsider-dominated board structure. While private-controlled enterprises are more efficient in constituting board structure, CEOs of state-controlled enterprises have more bargaining power over board structure.